A case of abortion consequent upon infection with Brucella abortus biotype 2 - Poole, Pauline M. (1972)
The case described here is that of young primigravida in normal health who, on serological evidence, contracted acute brucellosis, and subsequently aborted spontaneously, Br. abortus biotype 2 being isolated from the amniotic fluid.